2017
DOI: 10.1042/ns20160005
|View full text |Cite
|
Sign up to set email alerts
|

Conventional protein kinase C in the brain: 40 years later

Abstract: Protein kinase C (PKC) is a family of enzymes whose members transduce a large variety of cellular signals instigated by the receptor-mediated hydrolysis of membrane phospholipids. While PKC has been widely implicated in the pathology of diseases affecting all areas of physiology including cancer, diabetes, and heart disease -it was discovered, and initially characterized, in the brain. PKC plays a key role in controlling the balance between cell survival and cell death. Its loss of function is generally associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 115 publications
1
62
0
Order By: Relevance
“…PKC consists of a gene family divided into three classes: conventional PKCs α, β, and γ; novel PKCs δ, ε, η, and θ; and atypical PKCζ and PKCι/λ (human PKCι and rodent PKCλ are orthologous genes) (11, 12). Most PKCs consist of a regulatory domain and a catalytic domain.…”
mentioning
confidence: 99%
“…PKC consists of a gene family divided into three classes: conventional PKCs α, β, and γ; novel PKCs δ, ε, η, and θ; and atypical PKCζ and PKCι/λ (human PKCι and rodent PKCλ are orthologous genes) (11, 12). Most PKCs consist of a regulatory domain and a catalytic domain.…”
mentioning
confidence: 99%
“…It has been documented that following insulin binding to the receptor, in addition to Akt activation, some isoforms of PKC such as PKC ζ and PKMζ can be activated. The activation of these PKC isoforms, called atypical PKC and highly expressed in the brain, results in GSK3β phosphorylation on Ser9 residue and inactivates it . The effect of MA administration on atypical PKC function is less studied, but few studies indicated that MA administration caused PKMζ inactivation in hippocampus, which is associated with memory impairments, whereas in striatum it activates PKC ζ and PKMζ followed by increases in tyrosine hydroxylase and DAT .…”
Section: Discussionmentioning
confidence: 99%
“…PKC enzymes are regulated at the level of structure, function and subcellular localization [1][2][3][4][5][6][7][8][9]. PKC enzyme dysfunction has been linked to many human disease pathologies, including cancer, diabetes and heart disease [10][11][12][13][14][15][16][17]. PKC modulates aspects of cellular physiology, such as angiogenesis, cellular motility, proliferation, differentiation and apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Differential expression and activity of PKC has been linked to most types of cancer, including carcinomas (e.g., breast, colorectal), sarcomas (e.g., glioma), lymphomas (e.g., diffuse large Bcell lymphoma) and leukemias [10][11][12][13][14][15]. Generally, loss of PKC function has been linked to cancer, whereas enhanced activity has been linked to neurodegeneration [16]. Many groundbreaking investigations during the last two decades have suggested that PKC enzymes have novel therapeutic potential as drug targets in different cancers, heart failure and neurodegenerative diseases [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation